Effect of Lower Versus Higher Protein Content in Infant Formula Through the First Year on Body Composition from 1 to 6 Years: Follow‐Up of a Randomized Clinical Trial. Issue 7 (22nd June 2018) - Totzauer, Martina; Luque, Veronica; Escribano, Joaquin; Closa‐Monasterolo, Ricardo; Verduci, Elvira; ReDionigi, Alice; Hoyos, Joana; Langhendries, Jean‐Paul; Gruszfeld, Dariusz; Socha, Piotr; Koletzko, Berthold; Grote, Veit; et al.
Abstract : Objective: The objective of this study was to investigate the effect of lower protein (LP) versus higher protein (HP) content in infant formula on body composition from 3 months to 6 years. Methods: In a multicenter, double‐blind European trial, healthy infants ( N  = 1, 090) were randomly assigned to different protein content formulas (upper [HP] and lower [LP] limits of the European Union regulations in 2001) during the first year; breastfed infants ( N  = 588) were recruited for reference values. Weight, height, and triceps and subscapular skinfold (SF) thickness were measured repeatedly ( N  = 650 at 6 years), and body composition was estimated (Slaughter). The 99th percentile of fat mass index reference data were used to assess excess body fat at 6 years. Results: At 2 and 6 years, the study observed greater sum of SFs (Δ 2 years: 0.5 mm, P  = 0.026, Δ 6 years: 0.6 mm, P  = 0.045), fat mass index (Δ 2 years: 0.12 kg/m², P  = 0.008, Δ 6 years: 0.15 kg/m², P  = 0.011), and fat‐free mass index (Δ 2 years: 0.17 kg/m², P  = 0.003, Δ 6 years: 0.18 kg/m², P  = 0.010) in the HP group compared with the LP group. At 6 years, the HP group had a twofold higher risk than the LP group for excess body fat (adjusted odds ratio: 2.13, P  = 0.019). Conclusions: Infant formula with HP levels induced greater fat mass in children from 2 to 6 years. Lowering the protein content of infant formula may result in a healthier body composition in early childhood.